Consciousness alterations in a cohort of young Swiss men: Associations with substance use and personality traits - Deligianni, Marianthi Lousiana; Studer, Joseph; Gmel, Gerhard; Khazaal, Yasser; Bertholet, Nicolas (Frontiers in Psychiatry, 2023)
Background Substance-induced consciousness alterations (CA) have mainly been studied among users of psychedelics but not among people using street drugs. Aims Explore occurrences of three different types of substance-induced CA [ego dissolution (ED), visual pseudo-hallucinations (VPH), anxiety/paranoia (A/P)] and their perceived influences on life, together with their associations with substance use and personality correlates in a general population sample of 25-year-old men. Methods 2,796 young Swiss men lifetime substance users completed a self-report questionnaire including history of use (never, former, and current) of different substances categories (psychedelics, cocaine, psychostimulants, ecstasy, MDMA, and other drugs), substance-induced ego dissolution (ED), visual pseudo-hallucinations (VPH) and anxiety/paranoia (A/P), the influence of these CA experiences on life, and personality traits (sensation seeking, sociability, anxiety-neuroticism, and aggression–hostility). Results 32.2% reported at least one CA (i.e., ED, VPH or A/P), with 20.5% reporting ED, 16.7% VPH, and 14.6% A/P. Former and current use of psychedelics and ketamine was significantly associated with occurrences of all three types of CAs and with a positive influence of CA on life. Associations between the former and current use of other substances and the different types of CA were less consistent, and perceived influences on life were not statistically significant. Sociability was negatively associated with occurrences of all three types of CA. Positive associations were found between anxiety–neuroticism and ED and A/P, between aggression–hostility and A/P, and between sensation seeking and ED and VPH. Conclusion This study supports the potential for psychedelics to induce CAs perceived as beneficial to life among people using street drugs, possibly reflecting the mechanism underlying the therapeutic potential of psychedelics.